Ions Transport in Electrochemical Energy Storage Devices at Low Temperatures. (29th December 2021) - Sun, Yinglun; Liu, Bao; Liu, Lingyang; Yan, Xingbin
Abstract: The operation of electrochemical energy storage (EES) devices at low temperatures as normal as at room temperature is of great significance for their low‐temperature environment application. However, such operation is plagued by the sluggish ions transport kinetics, which leads to the severe capacity decay or even failure of devices at low‐temperature conditions. In this review, the difficulties of ions transport in electrolyte, electrolyte/electrode interface, and electrode material at low temperatures are discussed in depth, and the reported strategies to solve the corresponding problems are surveyed subsequently. Finally, the views on how to build high‐performance low‐temperature‐available EES devices as well as their development directions are put forward. Abstract : This review systematically analyzes the challenges of ion transport in electrolytes, electrolyte/electrode interface, and electrode material at low temperatures, and the reported strategies to solve the corresponding problems are surveyed subsequently. Finally, how to construct low‐temperature electrochemical energy storage devices with satisfactory performance and their future development direction are put forward.